Case Report: The importance of genetic counseling for families with hyperinsulinism - Sanders, Victoria R.; Lord, Katherine; Sigal, Winnie M.; McKnight, Heather; Adzick, N. Scott; States, Lisa J.; Bhatti, Tricia; De Leon, Diva D. (Frontiers in Pediatrics, 2025)
Congenital hyperinsulinism (HI) is the most common cause of persistent hypoglycemia in infancy. Genotype-phenotype correlations directly inform medical care for patients. Understanding the genetic etiology also allows accurate genetic counseling to be provided, illustrated by two families following a diagnosis of HI. A newborn had hypoglycemia at birth and was diagnosed with focal HI due to a paternally inherited recessive ABCC8 variant. Years later the paternal half-sibling was diagnosed with HI. Testing revealed compound heterozygous ABCC8 variants, consistent with diffuse disease. Following testing, the father's partner(s) should have been offered carrier testing. However, the parents were unaware that future children could be at increased risk of HI. The second family's son was diagnosed with HI in infancy and genetic testing identified a heterozygous recessive ABCC8 variant. Parental testing revealed both parents carried this variant. Focal HI was subsequently confirmed. This family's 1/4 chance to have a child with diffuse HI was significantly higher than the 1/540 chance their child could have focal HI. Understanding the etiology of a patient's HI not only allows for appropriate medical management but has important reproductive implications for the family. Genetic counseling is an important component of the multidisciplinary care received by every family with HI.